ANALISIS FAKTOR PENYEBAB ANAK PUTUS SEKOLAH DI DESA SERUMPUN BULUH KECAMATAN TEBAS KABUPATEN SAMBAS - yarso, Ariadi; Bahari, Yohanes; Asrianti, Nuraini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this thesis is the analysis of the factors causing dropouts in the whole village of tebas in the district of Sambas, Sambas, The purpose of this study was to find out the factors that cause dropouts in the whole village of the tebas sub-district of Sambas district. This research was conducted with descriptive research methods using qualitative forms. The research technique used was direct communication techniques and documentary study techniques with the results of the research as follows: 1) internal factors causing school dropouts. Based on the results of research on internal factors that cause school dropouts in this study because there is no willingness in the child himself to continue his education as children prefer to work. 2) external factors causing school dropouts. Based on the results of the research, the external factors that cause child dropouts are where the economic parents of children cannot finance because income from parents is only sufficient for their daily needs and lack of encouragement or motivation for children to continue their education. Keywords: Causes of School Dropouts,External Factors, Internal Factors